2018
DOI: 10.3390/pharmaceutics10040237
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Intracellular Delivery and Release of Hydrophilic Versus Hydrophobic Cargo from Mesoporous Silica Nanoparticles on 2D and 3D Cell Cultures

Abstract: Intracellular drug delivery by mesoporous silica nanoparticles (MSNs) carrying hydrophilic and hydrophobic fluorophores as model drug cargo is demonstrated on 2D cellular and 3D tumor organoid level. Two different MSN designs, chosen on the basis of the characteristics of the loaded cargo, were used: MSNs with a surface-grown poly(ethylene imine), PEI, coating only for hydrophobic cargo and MSNs with lipid bilayers covalently coupled to the PEI layer as a diffusion barrier for hydrophilic cargo. First, the eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 45 publications
1
4
0
Order By: Relevance
“…Similarly, PEI modified nanoparticles had strong colocalization with the TRITC channel and a smaller spread of intracellular release. Our previous reports have pinpointed the presence of MSN-PEIs in endosomes at 72 h after incubation supporting the necessity of the longer timeframe for intracellular release [ 77 ] and the release rate can be further promoted by utilizing ACA or SUC modification for more efficient cargo delivery in a shorter period in this case.…”
Section: Resultssupporting
confidence: 53%
“…Similarly, PEI modified nanoparticles had strong colocalization with the TRITC channel and a smaller spread of intracellular release. Our previous reports have pinpointed the presence of MSN-PEIs in endosomes at 72 h after incubation supporting the necessity of the longer timeframe for intracellular release [ 77 ] and the release rate can be further promoted by utilizing ACA or SUC modification for more efficient cargo delivery in a shorter period in this case.…”
Section: Resultssupporting
confidence: 53%
“…Therefore, silica nanoparticles have been recently used in a human trial for patients with melanoma and have shown strong implications in cancer diagnosis (Phillips et al, 2014). An interesting feature of MSNs is that it can encapsulate both hydrophilic and hydrophobic molecules with similar loading efficiency owing to extensively available pores (Slowing et al, 2008; Desai et al, 2018; Xu et al, 2018). Majority of chemotherapeutics and nutraceuticals with anticancer potential are hydrophobic in nature and as is the case of MSNs have been frequently used to demonstrate delivery of such substances.…”
Section: Introductionmentioning
confidence: 99%
“…[ 42 ] However, an increased hydrophobicity of the overall drug carrier system, with a higher amount of hydrophobic drug in the carrier, would lead to a decreased or delayed release of drugs as a result of irreversible drug carrier interaction. [ 43 ]…”
Section: Resultsmentioning
confidence: 99%